Highly reliable switched reluctance motor for the traction electric drive system of railway rolling stock - E. E. Miroshnichenko (Омский научный вестник)
The main purpose of this work is to create conditions for the use of switched reluctance motor in the traction electric drive system of rolling stock by increasing the reliability of its bearings. The object of the study is the traction switched reluctance motor. The task has been set, which consists in developing an algorithm that allows to calculate the characteristics of the traction switched reluctance motor at the stages of design and production, taking into account the forces of a oneway magnetic attraction. The forces of one-way magnetic attraction, arising in the air gap of the electric motor with two types of its non-uniformity are studied. A proposal has been made to limit the force of the one-way magnetic attraction to a force at a permissible residual imbalance. As a result, an algorithm for determining the characteristics of the traction switched reluctance motor is unique in its kind, which makes it possible to reduce the effect of forces of the one-way magnetic attraction on bearings. The use of switched reluctance motor with a long service life of bearings in the traction drive system will make it possible to obtain a new competitive rolling stock.